2012
DOI: 10.1007/s13246-012-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

Four dimensional radiotherapy: a review of current technologies and modalities

Abstract: Organ motion is a substantial concern in the treatment of thoracic tumours using radiotherapy. A number of technologies have evolved in order to address this concern in both the fields of CT imaging and radiation delivery. This review paper investigates the technologies which have been developed for the delivery of radiotherapy as well as the accuracy and workload implications of their use. Treatment techniques investigated include: breath hold, breath gating, robotic compensation and MLC manipulation. Each te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Internal organ motion caused by respiration or heartbeat is considerable. It is crucial to verify reproducibility of target location prior to treatment for lung and abdominal cancer patients [1][2][3]. Recently, the external and surface monitoring systems, such as RPM and OSMS (Varian Medical System, Palo Alto, USA), were used for patient positioning in radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Internal organ motion caused by respiration or heartbeat is considerable. It is crucial to verify reproducibility of target location prior to treatment for lung and abdominal cancer patients [1][2][3]. Recently, the external and surface monitoring systems, such as RPM and OSMS (Varian Medical System, Palo Alto, USA), were used for patient positioning in radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This information might be used for example to gate the beam or to adapt the treatment delivery in real time in the case of tumor tracking. 8,9 To address this need, several platforms have been developed to enable real time tumor position monitoring. Some of the earliest approaches to this were to utilize the MV imaging systems typically integrated on modern linacs to monitor the location of implanted fiducials within the beam portal throughout the treatment delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Image guided radiation therapy has technically achieved minimization of the setup margin, and thus the optimization of the ITV margin is an important factor in the determination of the planning target volume. Four-dimensional CT (4DCT) is one of the most important techniques to determine the ITV margin for RT planning 9 . Several studies that reported on esophageal tumor motion using 4DCT have been published 10, 11, 12, 13, 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%